Our children, their children confronting racial and ethnic differences in American juvenile justice - Hawkins, Darnell Felix, 1946-; Kempf Leonard, Kimberly (Chicago, Ill. : University of Chicago Press, 2005)
Researchers argue that a second-rate and increasingly punitive juvenile justice system is allowed to persist since many believe it is designed for children in other ethnic and socioeconomic groups. Contributors look at the effects on juvenile justice of suburban sprawl.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Juvenile justice, Administration of -- United States; Discrimination in juvenile justice administration -- United States; Crime and race -- United States; True Crime; United States of America, USA; Society & culture: general; Social services & welfare, criminology; Juvenile offenders; Jurisprudence & general issues